Embodying the pain and cruelty of others - Shapiro-Phim, Toni (International journal of transitional justice, 2020)
A ground-breaking performing arts-centered reparations project of the Extraordinary Chambers in the Courts of Cambodia - also known as the Khmer Rouge Tribunal - is entitled Phka Sla. The Phka Sla initiative was proposed by survivors of the practice of forced marriage under the Khmer Rouge. While organizations collaborating on Phka Sla are assessing the impact of its innovative dance drama, exhibition and other activities on audiences and survivors, this article offers initial observations regarding the impact of embodying survivor testimony on the artists themselves.